Development of a large‐volume human‐derived adipose acellular allogenic flap by perfusion decellularization. Issue 2 (19th May 2018) - Giatsidis, Giorgio; Guyette, Jacques P.; Ott, Harald C.; Orgill, Dennis P.
Abstract: In reconstructive surgery, transfer of patients' tissue (autologous flaps) is routinely used to repair large soft tissue defects caused by surgery, trauma, chronic diseases, or malformations; unfortunately, this strategy is not always possible and often creates a secondary defect in the donor site of the tissue. Tissue‐engineered synthetic flaps are currently unable to repair clinically‐relevant, large‐volume defects; allogenic flaps from cadaveric donors could provide a ready‐to‐use biological alternative if treated with methods to avoid the immune‐rejection of the donor's cells. Here, we describe the successful decellularization of a large (> 800 cc) human‐derived adipose flap through a perfusion apparatus; we demonstrate the complete removal of the immunogenic cellular components of the flap with the retention of its structural components and vascular network. Our aim is to obtain a universally compatible, off‐the‐shelf acellular allogenic flap that could be recellularized with cells from recipient patients to provide a tissue‐engineered allogenic/autologous alternative for reconstruction of large‐volume soft‐tissue defects.